Correlation of Quadriceps Angular Biomechanics to Anxiety in Amateur Women Football Athletes : Injury Risk Analysis - Resvita Aulia Putri; Mohammad Zaky; Unun Umaran (Universitas Negeri Semarang, 2025)
Injury prevention in female football athletes requires a multidimensional approach that integrates both biomechanical and psychological assessments. This research aims to examine the relationship between the quadriceps angle (Q-angle) and competitive anxiety in amateur female football players, with a focus on understanding the impact of Q-angle as an injury risk factor on anxiety levels. The importance of this study stems from the global rise of female participation in football, which is accompanied by a high incidence of lower extremity injuries, particularly among adolescents—a group that is physically and emotionally vulnerable. A total of eleven female athletes aged 14–21 years participated in the study. Q-angle measurements were conducted using image-based digital goniometry (KINOVEA®), whereas the Sport Anxiety Scale-2 (SAS-2) was utilized to assess levels of anxiety both before and after match participation. The findings revealed a non-significant decrease in anxiety scores following match play (from 35.23 ± 7.21 to 32.28 ± 8.49; p = 0.076), which may suggest a reduction in anticipatory stress after real-game involvement. Q-angle values varied widely from 9.5° to 29°, with several athletes exhibiting angles outside the normative female range of 15°–20°, indicating a possible increased risk for lower-extremity injuries. Even though a meaningful association was not established between the Q-angle measurements and anxiety levels, the occurrence of extreme readings in both areas among specific individuals suggests a potentially compounded injury risk that should be further investigatedIn spite of constraints such as a limited number of participants and the use of a cross-sectional study design, this research underscores the practical utility of low-cost, field-friendly tools for early detection of biomechanical and psychological injury risk factors. The results support the integration of dual-domain screening into injury prevention programs for adolescent female football players.